Genetic divergence among populations and accessions of the spineless peach palm from Pampa Hermosa landrace used in the heart-of-palm agribusiness in Brazil - Alessandro Alves-Pereira; Charles R. Clement; Doriane Picanço-Rodrigues (Genetics and Molecular Biology, 2012)
Although originally domesticated for its fruit, exploitation of the peach palm (Bactris gasipaes Kunth) in the production of gourmet heart-of-palm has also become an important activity, hence the need for improved material for large-scale production, on employing the Pampa Hermosa landrace as the seed source. In this study 11 microsatellite markers were used to evaluate genetic divergence among 96 elite plants representing four populations of spineless peach palm from the above cited source. Genetic variability was high (H T = 0.82). The low levels of divergence [F ST (0.023), G ST' (0.005)] and the high number of migrants (Nm -3.8 to 52.2) indicated significant interpopulation gene flow. Some of the plants presented high levels of genetic divergence, but the plants were grouped independently of their geographic origins. When combined with morpho-agronomic evaluation, the results found could substantially contribute towards mounting an efficient tool for obtaining superior genotypes with wide genetic variability for improvement programs.